Waste Management Model Based on Community Participation Through Smokless Burn Barrel Technology - Julio Caesar Zambas; Krisyana Agung Saputro; Annida Nuriska Utami; Dede Abdul Muid; Erista Mutia; Dea Rahmawati; Susan Nurjannah; Rini Oktaviani Riswan; Eva Fathusyaadah; Iin Khairunnisa (Siber Nusantara of Community Service Review, 2026)
The problem of household waste management is still a major challenge, especially in areas that do not have an integrated management system. The practice of open burning that is commonly carried out by the community has a negative impact on the environment and health due to harmful gas emissions. This research aims to develop a waste management model based on community participation through the application of Smokeless Burn Barrel technology in Jayamekar Village, Sukabumi City. The method used is Participatory Action Research (PAR) which actively involves the community in the planning, implementation, observation, and reflection stages. Data collection techniques include observation, interviews, documentation, and Focus Group Discussions (FGD), with interactive qualitative data analysis. The results of the study show that the application of Smokeless Burn Barrel technology is able to significantly reduce the volume of waste and smoke emissions, as well as increase public awareness and participation in waste management. In addition, there has been a change in community behavior in sorting waste before processing. The resulting model consists of four main components, namely the identification of participatory problems, the implementation of appropriate technologies, changes in community behavior, and continuous evaluation. However, the sustainability of the program still requires further assistance and institutional strengthening. This research confirms that the integration of appropriate technology and community participation is an effective strategy in realizing sustainable waste management and has the potential to be replicated in other regions.